FACTORS AFFECTING AIRPORT EMPLOYEES COMMUTING MODE CHOICE IN SOEKARNO-HATTA INTERNATIONAL AIRPORT - AGGI ISWARI (NIM: 24216004), SHALLI
Ground access problems occur in most airports in developing countries, especially in large-scale airports that are not equipped with adequate inter-mode transport systems. However, so far, ground access research has tended to focus on passenger mode choices, not workers. In fact, the choice of working mode becomes an equally important issue. The problem of ground access is not only related to passengers as workers produce a large number of vehicle trips to/ from the airport each day which impact on airport traffic conditions. Workers have the freedom to choose a commuter mode based on consideration factors considered beneficial. In Indonesia there has been no research in the field of ground access which specifically develops a model of worker-based commuter mode. With this background, this study aims to determine the factors that affect the selection of commuter airport worker modes. The research location is Soekarno-Hatta International Airport. The research method used is a quantitative method based on a questionnaire survey to 280 workers at Soekarno-Hatta International Airport. The commuter mode used consists of two categories, namely private vehicles and public transport. The important things in this study is to know the proportion of the use of commuter mode, to understand the relationship between the socio-economic characteristics of workers and the characteristics of the movement of workers with the commuter mode. Then after the factors that influence the selection of commuter mode can be known by using logistic regression analysis (binary logistic regression). Based on the results of the study it can be concluded that workers tend to use private vehicles as a commuter mode used for daily work trips. Then the factors that influence the selection of commuter mode are gender, vehicle ownership, mileage, travel time, and fuel cost. The following logistic regression equation is formed: Ln P/(1-P)=-2,853-3,438 X1 -6,901 X9-0,403 X12+0,612 X13+0,000 X15 Keywords: ground access, mode choice, workers, commuting, airports